Effectiveness of Using Audio Visual Media in Improving Student Achievement in Mathematics Learning in Elementary Schools - Baso Intang Sappaile; Nur Fajrin Maulana Yusuf; Mardiati Mardiati; Masli Nur cahya Zoraida; Ediaman Sitepu (Journal Emerging Technologies in Education, 2024)
Background. Audio-visual media is media that contains elements of sound and images. It is useful for conveying information, knowledge, ideas, ideas in a more interesting way. The proper use of audiovisual media in accordance with the needs in education will be able to improve learning achievement. Audio visual media will help students in developing logical, critical, and creative thinking skills in solving problems. The use of audiovisual media in learning mathematics can improve student achievement in elementary school. This can be achieved as long as the use is effective and efficient. Purpose. This study aims to measure the effectiveness of using audio-visual media in improving student achievement in mathematics learning in elementary schools. This research will also be useful to find out the factors that influence the success of using audio-visual media. In addition, it is also to find out how far audiovisual media can help students in understanding mathematical concepts, increase learning motivation, and develop logical, critical, and creative thinking skills. Method. The method used in this research is quantitative. Quantitative method is a way of presenting data in the form of numbers. The data obtained is the result of the acquisition of responses. The data is taken from the distribution of questionnaires containing questions related to the effectiveness of the use of audio-visual media in improving student achievement in mathematics learning at the elementary school level. Results. The results of this study state that the use of audio visual in math learning in elementary schools can improve student achievement. The use of audiovisual media has a positive effectiveness in learning mathematics in elementary schools. The use of audiovisual media can improve student learning outcomes, concept understanding, ability to analyze, and interest in learning. However, the use of this media must also pay attention to certain factors in order to be effective. Conclusion This research can be concluded that audio visual media as a learning medium that contains elements of sound and images will be able to be used to convey information, knowledge, ideas, or ideas more interestingly. The use of audio-visual media in learning mathematics will help in improving students' concept understanding, interest, and learning outcomes.